ARK 2004 : AWI airborne Radio-Echo Sounding Data over Nothern and Central Greenland between North GRIP, NEEM, GRIP, and GISP2 ice core sites and Southwest Greenland (NorthGRIP project) - Heinrich Miller; Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system (Nixdorf et al., 1999) during the Arctic season of 2004. The profiles extend across the Northeast Greenland Ice Sheet betweenNorth GRIP, NEEM, GRIP, and GISP2 ice core sites and Southwest Greenland. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.